Cyclic stress-strain model for large-rupture strain fiber-reinforced polymer (LRS FRP)-confined concrete. (October 2021) - Bai, Yu-Lei; Mei, Shi-Jie; Li, Pengda; Xu, Junjie
Abstract: Large-rupture strain (usually larger than 5%) fiber-reinforced polymer (LRS FRP) composites are attractive materials for the seismic retrofit of concrete structures. Jacketing LRS FRP on concrete columns can effectively improve the ultimate strength and deformation of a concrete structure and make the concrete structure have excellent ductility and superior energy absorption capacity. In comparison with conventional FRP, the concrete under LRS FRP confinement experiences a more severe damage process when it is under large deformation. The confining pressure at the large deformation can alter the concrete plastic flow and significantly affect the cyclic stress-strain path of LRS-FRP confined concrete. This study evaluates the performance of existing cyclic models (e.g., unloading path, reloading path, and plastic strain) using a database including both traditional and LRS FRP-confined concrete. Through an analytical study on the cyclic response of LRS FRP-confined concrete, two key parameters (plastic strain and stress degradation) were found to significantly influence the cyclic behavior of LRS FRP-confined concrete. By defining these two critical parameters, a new cyclic stress-strain model was developed for LRS FRP confined-concrete with good performance. The proposed cyclic model was also applicable in predicting both post-peak strain hardening and softening behavior when used in a stiffness-based envelope model. Highlights: The database, including the cyclic stress-strain curves of LRS and conventional FRP confined concrete, is established. Severe damage condition of LRS-FRP confined concrete at large deformation region significantly affects its cyclic behavior. The plastic strain and stress degradation are the key factors affecting the cyclic behavior of LRS FRP-confined concrete. A design-oriented model is developed to predict the cyclic curves of LRS FRP-confined concrete with good accuracy.